An integrated transcriptome and physiological analysis of nitrogen use efficiency in rice (Oryza sativa L. ssp. indica) under drought stress - Wang, Yu; Zhang, Yufan; Qiao, Han; Zheng, Yutong; Hou, Xin; Shi, Liangsheng (Frontiers in Genetics, 2024)
Nitrogen is a critical nutrient vital for crop growth. However, our current understanding of nitrogen use efficiency (NUE) under drought remains inadequate. To delve into the molecular mechanisms underlying NUE under drought, a transcriptome and physiological co-expression analysis was performed in rice, which is particularly sensitive to drought. We conducted a pot experiment using rice grown under normal irrigation, mild drought stress, and severe drought stress. Compared to the normal treatment, drought stress led to a significant reduction in NUE across growth stages, with decreases ranging from 2.18% to 31.67%. Totals of 4,424 and 2,452 genes were identified as NUE-related DEGs that showed differential expressions (DEGs) and significantly correlated with NUE (NUE-related) under drought in the vegetative and reproductive stages, respectively. Interestingly, five genes involved in nitrogen metabolism were found in the overlapped genes of these two sets. Furthermore, the two sets of NUE-related DEGs were enriched in glyoxylate and dicarboxylate metabolism, as well as carbon fixation in photosynthetic organisms. Several genes in these two pathways were identified as hub genes in the two sets of NUE-related DEGs. This study offers new insights into the molecular mechanism of rice NUE under drought in agricultural practices and provides potential genes for breeding drought-resistant crops with high NUE.